The tragedy of Mariam, the fair queen of Jewry / her life / by one of her daughters ; edited by Barry Weller and Margaret W. Ferguson. - Cary, Elizabeth, Lady, 1585 or 1586-1639 (University of California Press, 1994)
The Tragedy of Mariam (1613) is the first original play by a woman to be published in England, and its author is the first English woman writer to be memorialized in a biography, which is included with this edition of the play. Mariam is a distinctive example of Renaissance drama that serves the desire of today's readers and scholars to know not merely how women were represented in the early modern period but also how they themselves perceived their own condition.
Keywords: Mariamne, -- consort of Herod I, King of Judea, -- approximately 57 B.C.-approximately 29 B.C. -- Drama.; Herod -- I, -- King of Judea, -- 73 B.C.-4 B.C. -- Drama.; Cary, Elizabeth, -- Lady, -- 1585 or 1586-1639.; Cary, Elizabeth, -- Lady, -- 1585 or 1586-1639; Herod -- I, -- King of Judea, -- 73 B.C.-4 B.C.; Mariamne, -- consort of Herod I, King of Judea, -- approximately 57 B.C.-approximately 29 B.C.; Dramatists, English -- Early modern, 1500-1700 -- Biography.; Women and literature -- England -- History -- 17th century.; Femmes et littérature -- Angleterre -- Histoire -- 17e siècle.; DRAMA -- English, Irish, Scottish, Welsh.; Dramatists, English -- Early modern -- Biography; Women and literature; England; 1600-1699; collective biographies.; Biographies; Drama; History; Tragedies.; Biographies.